The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/jth.13709
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐assisted versus conventional catheter‐directed thrombolysis for acute iliofemoral deep vein thrombosis: 1‐year follow‐up data of a randomized‐controlled trial

Abstract: Background In patients with acute iliofemoral deep vein thrombosis (IFDVT), catheter-directed thrombolysis (CDT) aims to prevent the postthrombotic syndrome (PTS). Adding intravascular high-frequency, low-power ultrasound energy to CDT does not seem to improve the immediate thrombolysis results but its impact on clinical outcomes at 12 months is not known. Patients/Methods In this randomized-controlled trial, 48 patients (mean age 50 ± 21 years; 52% women) with acute IFDVT were randomized to conventional CDT (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 37 publications
1
32
2
Order By: Relevance
“…Our results confirm the previous report from the pooled data of the randomized controlled BERNUTIFUL (BERN Ultrasound-assisted Thrombolysis for Ilio-Femoral deep vein thrombosis versUs standard catheter directed thromboLysis) trial, which reported an overall incidence of PTS at 12 months follow-up of 11%. [16] These results are in contrast with the relatively high incidence of PTS at 24 months in the interventional study arms of the CaVenT (41%) and ATTRACT (31%) trials, [3,10] which might be due to the much higher stent placement rate in the BERNUTIFUL trial (80%) and the present study. [16] Our study has several limitations.…”
Section: Ifdvtcontrasting
confidence: 78%
See 3 more Smart Citations
“…Our results confirm the previous report from the pooled data of the randomized controlled BERNUTIFUL (BERN Ultrasound-assisted Thrombolysis for Ilio-Femoral deep vein thrombosis versUs standard catheter directed thromboLysis) trial, which reported an overall incidence of PTS at 12 months follow-up of 11%. [16] These results are in contrast with the relatively high incidence of PTS at 24 months in the interventional study arms of the CaVenT (41%) and ATTRACT (31%) trials, [3,10] which might be due to the much higher stent placement rate in the BERNUTIFUL trial (80%) and the present study. [16] Our study has several limitations.…”
Section: Ifdvtcontrasting
confidence: 78%
“…During the study period, the stent placement rate in patients with IFDVT treated with early thrombus removal was 80%. [13,16] The registry and participant consent form were approved by the Swiss Ethics Committee on research involving humans. The study is registered on the National Institutes of Health website (ClinicalTrials.gov; identifier NCT02433054).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…9 In addition, other groups have recently published similarly low rates of PTS, albeit after 1e2 years, and this appears to be the experience of most mature centres. 10,11 This problem of randomizing patients to low volume centres, still on the learning curve, has plagued many trials of intervention vs. medical therapy. This is similar to the experience of the introduction of clot removal techniques for both coronary disease and stroke where a cycle of improvement in technique and repeat of trials made early clot removal the standard of care.…”
mentioning
confidence: 99%